IMPORTANCE AND MEASURES OF DISASTER MANAGEMENT IN LIBRARIES - Rehman, Ata ur (European Scientific Journal, ESJ, 2014)
The aim of this article is to explore the importance and measures that can be taken to avoid the man made disasters and minimize the effect of all types of natural disasters in the library. Current literature on disaster management will be received to determine the new trends in these fields. Disasters in libraries and other related information centers have become a common occurrence in the recent past in all parts of the world. These disasters are due to both man made and natural causes. Why Disaster Management is important? “Disaster management” includes disaster control planning. It also encompasses broader issues for a successful implementation. Recently the term “risk management” has been problems of known risks at source. Good disaster management com prevent fires floods, thefts etc from happening, and if they happen, their effect would be greatly minimized. Disaster control is properly structured and systematic plan which should be known by all staff. The staff should also know the risks involved and their roles in the event of an actual disaster situation. Disaster management is most important because of the value of the materials, services provided in the libraries and security measures which can be affected by them. Some of the material, physical facilities and human lives destroyed by the various disasters, in order to prevent great losses brought about by disasters, it is necessary to take precautions.